KARAKTERISTIK FISIKO KIMIA DAN SENSORIS TEPUNG KELAPA PADA BERBAGAI SUHU PENGERINGAN - Hidayat, Alif; Rahim, Abdul; Rostiati, Rostiati (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2023)
This study objective was to evaluate various drying techniques used to produce coconut flour from coconut pulp in order to assess its physico-chemical and organoleptic properties. The research was carried out at the Agroindustry Laboratory of the Faculty of Agriculture and the Chemistry Laboratory of the Faculty of Mathematics and Natural Sciences Tadulako University. This research was carried out from January to April 2021. The study was arranged using a completely randomized design and a randomized block design with one factor namely drying temperatures (40ºC, 50ºC, 60ºC, 70ºC and 80ºC). Each treatment was replicated 3 times. The results of the study showed that the best drying temperature based on the physico-chemical and sensory characteristics of coconut fluor was 70°C. The treatment at 70°C resulted in an average value of 3.64% moisture content, 1.86% ash content, 9.21% protein content, 51.68% fat content, and 26.24% fiber content for the coconut flour. Organoleptic analysis of coconut flour at 70°C showed a color score of 5.0 (slightly like), aroma score of 5.60 (slightly like), taste score of 4.68 (neutral), and texture score of 5.36 (slightly liked).